\(\mathcal{I}_{g*}\)-NORMAL AND \(\mathcal{I}_{g*}\)-REGULAR SPACES - Ravi, O.; Paranjothi, M.; Murugesan, S.; Padmasekaran, S. (Italian Journal of Pure and Applied Mathematics, 2015)
\(\mathcal{I}_{g^*}\)-normal and \(\mathcal{I}_{g^*}\)-regular spaces are introduced and various characterizations and properties are given. Characterizations of normal, mildly normal, g*-normal and regular spaces are also given.